2017
DOI: 10.24085/jsaa.v5i2.2700
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Assisted Learning Programme: Supporting Students in High-Risk Subjects at the Mechanical Engineering Department at Walter Sisulu University

Abstract: The majority of the students who enroll at the Walter Sisulu University (WSU) Education and Training (2013, p. 17), further states that "students' support is crucial to ensure that students adapt to the demands of college life and that they can meet the demands of college programmes". Particularly in South Africa, the school environment might also contribute to poor student performance as a result of insufficient student support, and a lack of facilities and resources. In order to address this gap, a Peer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The SPAL sessions supported ECP participants beyond an academic level, as interviewees claimed that the formation of this camaraderie also addressed their transitional challenges. This finding is important as the pre-established outcomes and objectives of SPAL sessions are mostly focused on addressing academic challenges, whereas CPAL can accommodate wider-focused outcomes such as addressing social, pastoral and transitional matters (Makala, 2017). Furthermore, findings from this study imply that SPAL and its related activities could also support adapting to tertiary education and not merely only address academic and retention challenges.…”
Section: It Was Supportive … You Know You Could Have Insight Into How...mentioning
confidence: 77%
“…The SPAL sessions supported ECP participants beyond an academic level, as interviewees claimed that the formation of this camaraderie also addressed their transitional challenges. This finding is important as the pre-established outcomes and objectives of SPAL sessions are mostly focused on addressing academic challenges, whereas CPAL can accommodate wider-focused outcomes such as addressing social, pastoral and transitional matters (Makala, 2017). Furthermore, findings from this study imply that SPAL and its related activities could also support adapting to tertiary education and not merely only address academic and retention challenges.…”
Section: It Was Supportive … You Know You Could Have Insight Into How...mentioning
confidence: 77%
“…In recent years, there have been lots of researchers evaluating their learning performances in various disciplines, such as medical study (Burgess, McGregor, & Mellis, 2014;Herrmann-Werner et al, 2017), nursing study (McLelland, McKenna, & French, 2013;Williams, Olaussen, & Peterson, 2015;Williams & Reddy, 2016), radiography (Meertens, 2016), biology (Rayner & Papakonstantinou, 2018), geography (West, Jenkins, & Hill, 2017), mathematics (Duah, Croft, & Inglis, 2014), accounting (Marrone & Draganov, 2016;Sudhakar, Tyler, & Wakefield, 2016;Supple, Best, & Pearce, 2016), mechanical engineering (Qonda, 2017) and other challenging subjects of undergraduate programmes. However, not many longitudinal studies have been conducted on the subjects in business disciplines with Peer Assisted Learning support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Peer support 'helps students to realize and envision their self-identity as STEM [i.e., Science, Technology, Engineering or Mathematics] scholars with the potential to offer meaningful contributions to their disciplines' (Wilson et al, 2012: 154). Peer support has been identified as playing an even stronger role when the students are from underrepresented groups in technical and vocational fields (Bell et al, 2012;Holmegaard, Madsen and Ulriksen, 2014;Makala, 2017;Soldner, Rowan-Kenyon, Inkelas, Garvey and Robbins, 2012). Studies have found that tutors and other student assistants are most effective when they are from similar backgrounds as the students whom they support (Espinosa, 2011), for example, under-represented students in STEM disciplines and fields felt 'validated within a community that affirmed their presence and abilities to succeed in fields they select[ed]' (Palmer, Maramba and Dancy, 2011: 501).…”
Section: A Brief Overview Of the Literature On Peer Support In Higher...mentioning
confidence: 99%